An alternative method of hedge algebra-based controller for water level control system in a thermal power plant - Hong Quang, Nguyen (International Journal of Engineering and Technology, 2019)
The control structure of steam boiler system is one of the most complex systems where required with many control loops and multiple pa-rameters. It is necessary for the controller used for this system to ensure the efficiency of the steam, so the control approaches need to be improved regularly. While some controllers such as PID, Fuzzy logic control have been applied successfully, the Hedge Algebra algorithm is a soft-computing tool developed from fuzzy logic that can be applied and calculated effectively with high accuracy in the control aspect. The paper presents an application of the controller based on hedge algebra in the control of the water level for the thermal power plant. Sys-tem quality is assessed through simulation and comparison with the traditional PID controller. Â